The linear shade guide design of Vita 3D-master performs as well as the original design of the Vita 3D-master - Corcodel, Nicoleta; Rammelsberg, Peter; Jakstat, H.; Moldovan, O.; Kappel, Stefanie; Hassel, Alexander J. (Journal of oral rehabilitation, 2010)
Visual tooth colour assessment by use of the Vita 3D-Master(®) (3D; Vita Zahnfabrik, Bad Säckingen, Germany) is well documented. To improve handling, a new linear arrangement of the shade tabs has been introduced (LG; Linearguide 3D-Master(®) ). The purpose of this study was to investigate whether the linear design has an effect on shade matching. Fifty-six students underwent identical, theoretical and practical training, by use of an Internet learning module [Toothguide Training Software(®) (TT)] and a standardised training programme [Toothguide Training Box(®) (TTB)]. Each student then matched 30 randomly chosen shade tabs presented in an intra-oral setting by a standardised device [Toothguide Check Box(®) (TCB)]; 15 matches were made using the 3D and 15 using the LG shade guide system, under a daylight lamp (840 matches for each guide). It was recorded to what extent the presented and selected shade tabs, or the lightness group of the tabs, matched, also the needed time for colour matching. The results showed that 35% of perfect matches were observed for the 3D and 32% for the LG. The lightness group was correct in 59% of cases for 3D and 56% for LG. Mean time needed for matching of tabs and lightness group was no different between groups (no significant difference for any assessment). Within the limitations of the study design, the colour assessment with regard to performance and time needed in shade matching was not different with the LG or the 3D. Therefore, the user should choose which shade tab arrangement is more applicable.
Gesehen am 16.06.2023